1987
DOI: 10.1177/089124387001004005
|View full text |Cite
|
Sign up to set email alerts
|

How Women Reshape the Prison Guard Role

Abstract: This article describes the innovative job performance strategies used by women who work as guards in men's prisons. It suggests that women guards perform the job differently from men guards not only because women face structural and discriminatory barriers on the job but also because most women bring to the job a set of prior experiences, skills, and abilities different from those of most men. One of the reasons women may fail to receive positive performance evaluations in jobs traditionally held by men is tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 7 publications
4
50
0
1
Order By: Relevance
“…Any research attempting to identify gender differences is therefore vulnerable to this problem of measuring women's effectiveness. Zimmer (1987) believes that the 'structural and discriminatory barriers' that may exist for women in such environments and the different experiences and skills they hold mean women will always perform the job differently from men. So, women may never perform their duties similarly to men and, if compared with men, will therefore always be labelled as less effective.…”
Section: Introductionmentioning
confidence: 98%
“…Any research attempting to identify gender differences is therefore vulnerable to this problem of measuring women's effectiveness. Zimmer (1987) believes that the 'structural and discriminatory barriers' that may exist for women in such environments and the different experiences and skills they hold mean women will always perform the job differently from men. So, women may never perform their duties similarly to men and, if compared with men, will therefore always be labelled as less effective.…”
Section: Introductionmentioning
confidence: 98%
“…Various consistent themes emerged across gender. Male officers reported that their chances of being promoted were quite good (Lovrich and Stohr 1993), while female officers believed they were at a disadvantage (Belknap 1991;Crouch 1985;Jurik 1985;Zimmer 1986Zimmer , 1987Zupan 1992). Gender differences in perceptions of not being promoted were attributed to various issues.…”
Section: Gender Perceptions and The Promotional Processmentioning
confidence: 96%
“…Benefits of having females in a correctional setting include having a calming effect on inmates, and the introduction of positive female role models to male inmates who likely have had prior dysfunctional interactions with the opposite sex (Crouch 1985;Kissel and Katsampes 1980;Lovrich and Stohr 1993;Parisi 1984). Female officers often use different types of skill sets such as listening to inmates' problems, using open dialog, humor, and gentle persuasion in conversations (instead of aggression and physical force) to resolve intimate conflicts and other problems that occur in a correctional setting (Kissel and Katsampes 1980;Lovrich and Stohr 1993;Pogrebin and Poole 1998;Zimmer 1986Zimmer , 1987. Some findings also suggest that female officers positively view their occupation from a service-oriented role as rehabilitators more so than merely guards (Crouch 1985;Jurik 1985;Walters 1992).…”
Section: Female Employment In Correctionsmentioning
confidence: 98%
See 2 more Smart Citations